Food Poisoning Outbreak Prevention Model: The Role of Health Workers for Food Safety of Catering Owners - Rapida Saragih; Hardisman Dasman; Ahmad Syafruddin Indrapriyatna; Finny Fitry Yani; Nur Indrawaty Lipoeto; Husna Yetti; Ilmiawati Ilmiawati; Harnavi Harun (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Food poisoning is a serious problem that can have an impact on public health. This incident occurs when the food consumed is contaminated by bacteria, viruses, parasites or hazardous chemicals. Medan City is an area where food poisoning incidents occur every year. The purpose of this study is to examine the importance of the role of health workers in preventing extraordinary incidents of food poisoning. This study is an exploratory qualitative study through a phenomenological approach. The location of the qualitative research was conducted at the Medan City Health Office, in the working area of the Medan Area, Medan Deli, and Tuntungan Health Centers which were designated as research areas. Data collection was carried out through several main techniques, namely in-depth interviews with interview guidelines, observation, and focus group discussions. While The data processing process involves several stages, namely starting with data transcription, data reduction, and data presentation. The final stage is drawing conclusions and verification. Data analysis uses a triangulation approach to increase the credibility of research results, including data triangulation, observer triangulation, theory triangulation, and triangulation Methods. This study was conducted in 2024 with informants including the Disease Prevention and Control Team and the Public Health Team, the head of the health center. The results of this study indicate that efforts to prevent food poisoning outbreaks have not been going well. Where the cause is the suboptimal role of health workers in monitoring and evaluation due to limited human resources, in addition to the lack of training related to prevention and handling and the absence of a special policy for food poisoning outbreaks. This prevention can only be implemented if there is collaboration between health workers and catering owners to add a shared commitment to food safety. and it is necessary to carry out comprehensive coaching and supervision efforts. Keywords: Prevention, Extraordinary Events, Food Poisoning, Health Workers